Social Orientation: Problem Behavior and Motivations Toward Interpersonal Problem Solving Among High Risk Adolescents - Kuperminc, Gabriel P. (2001)
A model of problematic adolescent behavior that expands current theories of social skill deficits in delinquent behavior to consider both social skills and orientation toward the use of adaptive skills was examined in an ethnically and socioeconomically diverse sample of 113 male and female adolescents. Adolescents were selected on the basis of moderate to serious risk for difficulties in social adaptation in order to focus on the population of youth most likely to be targeted by prevention efforts. Structural equation modeling was used to examine cross-sectional data using multiple informants (adolescents, peers, and parents) and multiple methods (performance test and self-report). Adolescent social orientation, as reflected in perceived problem solving effectiveness, identification with adult prosocial values, and self-efficacy expectations, exhibited a direct association to delinquent behavior and an indirect association to drug involvement mediated by demonstrated success in using problem solving skills. Results suggest that the utility of social skill theories of adolescent problem behaviors for informing preventive and remedial interventions can be enhanced by expanding them to consider adolescents’ orientation toward using the skills they may already possess.